TUJUAN AKUNTANSI PERTANIAN BERBASIS FILOSOFI RANGKIANG - Khadijah Ath Thahirah; Dedi Fernanda (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2021)
Penelitian ini bertujuan untuk menemukan tujuan dari akuntansi pertanian yang dimiliki masyarakat Minangkabau berbasis filosofi rankiang. Metode yang digunakan adalah analisa terhadap makna-makna yang terkandung pada fungsi dan bentuk dari beberapa jenis rangkiang. Penelitian ini menemukan bahwa masyarakat Minangkabau memiliki praktik akuntansi pertanian yang tidak bertujuan untuk memenuhi kepentingan diri sendiri apalagi mengutamakan laba, namun lebih mengutamakan kemakmuran bersama dalam masyarakat. Bahkan rangkiang hadir sebagai pendukung masyarakat dalam menunaikan kewajiban agama Islam yaitu zakat. Abstract: The Goals of Agricultural Accounting Based on the Rangkiang Philosophy. This study aims to find the objectives of agricultural accounting owned by the Minangkabau community based on the rankiang philosophy. The method used is an analysis of the meanings contained in the functions and forms of several types of rangkiang. This study found that the Minangkabau people have agricultural accounting practices that do not aim to fulfill their own interests, let alone prioritize profit, but prioritize mutual prosperity in society. Even cheerful is present as a supporter of the community in fulfilling the Islamic religious obligation, namely zakat Abstract This study aims to find the objectives of agricultural accounting practices that the Minangkabau community had in the past. The four types of rangkiang with different functions and forms are believed to have important philosophies and meanings for the Minangkabau people. The method used in this research is to trace the meanings of the functions and forms of various types of rankiang buildings. This study found that the Minangkabau community has agricultural accounting practices that do not aim to fulfill their own interests, prioritize profit, but prioritize mutual prosperity in society. Even rangkiang is present as a supporter of the community in fulfilling the Islamic religious obligation, namely zakat.